Challenges in Implementing the Concept of Public Internal Financial Controls in the Public Sector of Bosnia and Herzegovina (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The requirements of joining the European Union have imposed the need for candidate countries to reconsider their control mechanisms related to the use of public funds, and to assess the extent to which they ensure compliance with the principles of good governance, including economy, efficiency and effectiveness. During the pre-accession negotiations, candidate countries are expected to set up and develop internal financial control systems to prepare for all the challenges they face by joining the European Union and participating in EU funds. Availability of EU funds for one country largely depends precisely on the quality of the established internal financial control system. In order to facilitate the establishment of such a system, the European Commission has developed a concept called Public Internal Financial Control based on international standards and best practices of EU countries. The aim of this paper is to examine the extent to which the Public Internal Financial Control concept has been implemented in the public sector of Bosnia and Herzegovina, what challenges public institutions in B&H currently face in this context, and what are the recommendations for overcoming identified challenges.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.